Unpacking Overconfident Behavior When Betting on Oneself - Abdellaoui, Mohammed; Bleichrodt, Han; Gutierrez, Cédric (Management Science, 2024)
Overconfident behavior, the excessive willingness to bet on one’s performance, may be driven by optimistic beliefs and/or ambiguity attitudes. Separating these factors is key for understanding and correcting overconfident behavior, as they call for different corrective actions. We present a method to do so, which we implement in two incentivized experiments. The first experiment shows the importance of ambiguity attitudes for overconfident behavior. Optimistic ambiguity attitudes (ambiguity seeking) counterbalanced the effect of pessimistic beliefs, leading to neither over- nor underconfident behavior. The second experiment applies our method in contexts where overconfident behavior is expected to vary: easy versus hard tasks. Our results showed that task difficulty affected both beliefs and ambiguity attitudes. However, although beliefs were more optimistic for relative performance (rank) and more pessimistic for absolute performance (score) on easy tasks compared with hard tasks, ambiguity attitudes were always more optimistic on easy tasks for both absolute and relative performance. Our findings show the subtle interplay between beliefs and ambiguity attitudes: they can reinforce or offset each other, depending on the context, increasing or lowering overconfident behavior. Yuval Rottenstreich, behavioral economics and decision analysis. Funding: This work was supported by HEC Paris research budget and Bocconi junior researchers’ grants. Supplemental Material: The data and online appendix are available at https://doi.org/10.1287/mnsc.2021.00165 .